The re-initiation mechanism of detonation diffraction in a weakly unstable gaseous mixture. (25th July 2020) - Shi, Lisong; Uy, Ken Chun Kit; Wen, Chih Yung
Abstract : Abstract : Numerical simulations were performed to investigate the re-initiation mechanism of a diffracted detonation wave near the critical channel width for a weakly unstable gas. Two scenarios were examined: diffraction of a planar detonation wave and of a cellular detonation wave inside the inlet channel. The results revealed that the critical channel width predicted using a cellular detonation wave is smaller than that predicted using a planar detonation wave. The re-initiation mechanisms are described in detail by tracing massless particles along both the plane of symmetry and the re-initiation path. For planar detonation diffractions, a compression wave is formed in the far field behind the diffracted shock. Re-initiation is closely related to the amplification of this compression wave and its coalescence with the diffracted shock. Depending on the inlet channel width, the strength of the reflected rarefaction wave is responsible for weakening the strength of the compression wave and its coalescence with the diffracted shock, consequently hindering the reaction of particles behind the diffracted shock wave. In cellular cases, the continuous collisions of transverse waves, which generate local explosion sites, sustain detonation wave propagation.